Trabecular bone modeling methodology using geometric representations - Osvaldo Ruiz-Cervantes (Ingeniería. Investigación y Tecnología, 2017)
In this paper is presented a methodology to generate two-dimensional models of cancellous bone from images, with the main objective to achieve a closer representation to reality, in terms of the geometries that can be obtained. The methodology mainly uses Python™ language programming to establish instructions for using Abaqus™ graphical tools and therefore automatically generate the trabecular structure from the original image. As a ęrst step, each tra - becula of the image is idealized as an ellipse and each one is taken as basis for generating the geometries of pores and trabeculae in the model. A simulation of a compression test is also presented for three models made with this methodology, where ęnite element software was used. It is concluded that the methodology allows geing a very similar trabecular structure to the real one.